Climate change and the risk of spread of the fungus from the high mortality of Theobroma cocoa in Latin America - Sania Ortega Andrade (Neotropical Biodiversity, 2017)
Cocoa (Theobroma cacao L. 1753) is a plant of great cultural, economic and ecological importance globally. By its structure and function maintains a wide variety of animal species. In Latin America, their crops are being affected by the disease called ‘frosty pod rot of cocoa’ caused by the fungus Moniliophthora roreri (Cif & Par) Evans. 2007, considered as the most destructive disease that attacks cocoa and kills it. The increase of temperature or precipitation because of warming global climate change could favor the fungus expansion to areas previously unaffected. We modeled the potential distribution for M. roreri and T. cocoa using MaxEnt and circulation model general HADCM3, A2a scenario with climatic variables for the present and the future (5, 35 and 65 years), in order to find sites suitable for monitoring to prevent the fungus spread, and to identify which variables determine the presence of M. roreri. The suitable areas for both species overlap from present to 2050, while they are different in 2080. M. roreri could extend from southern Ecuador to Venezuela, spread to westernmost Amazon, southwest Peruvian Amazon, and to the Peruvian-Bolivian border and the adjacent areas of Brazil. In both taxa the most influential variable seems to be precipitation of the wettest month. The Brazilian Amazon is the areas of South America with the largest plantations of T. cocoa, and therefore the most sensitive to the presence and proliferation of the fungus. For this reason we recommend to set up a monitoring system allowing early warning and control of incipient outbreaks that could eventually destroy Bolivian and Brazilian cocoa plantations.